2019
DOI: 10.5194/gmd-12-5113-2019
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of the uncertainties of global surface ocean CO<sub>2</sub> estimates using a machine-learning ensemble (CSIR-ML6 version 2019a) – have we hit the wall?

Abstract: Abstract. Over the last decade, advanced statistical inference and machine learning have been used to fill the gaps in sparse surface ocean CO2 measurements (Rödenbeck et al., 2015). The estimates from these methods have been used to constrain seasonal, interannual and decadal variability in sea–air CO2 fluxes and the drivers of these changes (Landschützer et al., 2015, 2016; Gregor et al., 2018). However, it is also becoming clear that these methods are converging towards a common bias and root mean square er… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(198 citation statements)
references
References 73 publications
7
173
0
Order By: Relevance
“…We test NN, XGBoost (XGB) and random forest (RF) regression. Our XGB and RF are similar to the GBM and ERT of Gregor et al (2019), respectively. The three approaches we test have different properties, advantages, and drawbacks.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…We test NN, XGBoost (XGB) and random forest (RF) regression. Our XGB and RF are similar to the GBM and ERT of Gregor et al (2019), respectively. The three approaches we test have different properties, advantages, and drawbacks.…”
supporting
confidence: 55%
“…Though RF does almost as well as XGB on the test data, it generalizes poorly. Gregor et al (2019) also found that the random forest method performs poorly in pCO 2 reconstruction.…”
Section: Discussionmentioning
confidence: 92%
“…Machine learning methods represent a promising way to fill these "observational gaps". They have the potential to predict, from variables systematically measured by autonomous platforms, variables still difficult to measure accurately and cost-effectively with these platforms (e.g., Gregor et al, 2019). Transfer functions such as multiple linear regressions (e.g., Velo et al, 2013;Carter et al, 2018) have therefore been developed to estimate biogeochemical variables.…”
Section: Introductionmentioning
confidence: 99%
“…The data-products are inter-and extrapolations of SOCAT data, and hence have higher correlation coefficients and lower RMSEs than the GOBMs. However, they also have RMSEs of 15-20 µatm (see also Gregor et al, 2019) and correlation coefficients of 0.8-1.0 with lower correlation values in the southern and northern extratropics ( Figure 9A, Supplementary Figures 1, 3-15 for individual models and data-products). Comparison on monthly time-scales is a common approach to measure misfit between estimated and observed pCO 2 (e.g., Le Quéré et al, 2018a;Friedlingstein et al, 2019;Gregor et al, 2019).…”
Section: Historical Simulation: Model and Data Comparisonmentioning
confidence: 98%
“…We argue that the detrended annual statistic is more informative for the evaluation of annual estimates of S OCEAN with the aim to robustly estimate the mean S OCEAN and multi-year variability. The monthly statistics, which are most commonly used to evaluate GOBMs and data-products (Rödenbeck et al, 2015;Friedlingstein et al, 2019;Gregor et al, 2019) quantify to a large extent the representation of the seasonal cycle. Based on our analysis of model-data mismatch, we conclude that misrepresentations of the seasonal cycle in GOBMs have little effect on the global annual estimate of S OCEAN .…”
Section: Lessons Learned From Pco 2 Data Mismatchmentioning
confidence: 99%